Open On-Limb Robot Locomotion Mechanism with Spherical Rollers and Diameter Adaptation - Tobar-Subía-Contento, Luz María; Mandow, Anthony; Gómez-de-Gabriel, Jesús Manuel (MDPI, 2024)
The rapid development of wearable technologies is increasing research interest in on-body robotics, where relocatable robots can serve as haptic interfaces, support healthcare measurements, or assist with daily activities. However, on-body mobile robotics poses challenges in aspects such as stable locomotion and control. This article proposes a novel small robot design for moving on human limbs that consists of an open grasping mechanism with a spring linkage, where one side holds a pivoting differential drive base (PDDB) with two spherical rollers, and the other side holds an actuated roller for grasping and stabilization. The spherical rollers maintain contact at three points on the limb, optimizing stability with a minimal number of rollers and integrating DC motors within. The PDDB wheels (spherical rollers) enable directional changes on limb surfaces. The combination of the open mechanism, the PDDB, and the spherical rollers allows adaptability to diameter variations along the limb. Furthermore, the mechanism can be easily put on or removed at any point along the limb, eliminating the need to slip the robot over the hand or foot. The kinematic model for the proposed mechanism has been developed. A cascade control strategy is proposed with an outer loop for stable grasping and an inner loop for trajectory adjustments using PDDB roller velocities. An on-limb robot prototype has been built to test its applicability to human arms. Simulation and experimental results validate the design.
Keywords: Interacción hombre-ordenador; On-body mobile robot; Physical human-robotic interaction; Spherical rollers; Grasping; Limb climbing robot